Compulsão Alimentar: será uma cirurgia bariátrica de revisão eficaz no tratamento após uma primeira cirurgia? - Francisca Mesquita Ribeiro e Campos (2022)
Binge eating is defined as eating an abnormally high amount of food in a short period of time, and must be accompanied by a subjective feeling of lack of control over eating. Indeed, binge eating is present in many morbidly obese patients who are candidates for bariatric surgery, and it is reported that this surgery may have a positive role in improving symptoms and decreasing the number of this episodes related to this disorder.Given the increasing number of revisional bariatric surgeries performed over the years, the aim of this narrative review is to investigate its effectiveness in binge eating, and to find out if it really has benefits, or if, on the other hand, it is more advantageous to opt for a psychosocial intervention, pre- or post-surgical, or both simultaneously. Using PubMed as a database, the study's search results included articles between 2017 and 2021 with the following querys: "Bariatric Surgery AND Binge Eating" and "Outcomes of Revisional Bariatric Surgery", and 42 articles were selected. The frequency of binge eating diagnosis had a small decrease (with no statistically significant differences) right after the first surgery, but a large decrease in the following 3 months, being significantly lower at 3, 6 and 12 months of follow-up. From the 1st year onwards, the results are not consensual: some articles showed that between the 1st and 2nd years after surgery, there was a significant increase in binge eating, but others showed that at 24 months of follow-up, binge eating episodes decreased by 13%. In the long term, these results remain unchanged. In regard to revision bariatric surgery, the percentage of patients involved in binge eating behaviors is higher. These patients also practice less physical activity, have less healthy eating habits and higher levels of psychological stress, when compared to first bariatric surgery. More studies are needed to assess the optimization of binge eating outcomes using revision bariatric surgery, after first bariatric surgery, as well as more studies comparing the effectiveness of this second surgery with simultaneous psychosocial therapy.